Sistem Informasi Badan Usaha Milik Desa Kasomalang Kulon Berbasis Web - Caca Arif Herdian; Yudha Koswara (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
BUMDes are business institutions owned and managed by the village community. BUMDes were established to improve the village economy and the welfare of the village community. In running their businesses, BUMDes can face various challenges, one of which is the problem of access to information. The purpose of this study is to develop a web-based information system as one solution to expand the reach of information access that can be seen by the general Indonesian public. The information system was developed using the PHP programming language with the CodeIgniter 4 framework, MySQL database, and Unified Modelling Language (UML) system modeling. The method used in system development is the waterfall method. The result of this research is the information system of the Kasomalang Kulon Village-Owned Enterprise, which has several features such as front-end pages including the home page, gallery articles, about, and back-end pages including the dashboard page, manage articles, manage galleries, and manage about